The Neurobiology of Postpartum Anxiety and Depression - Pawluski, Jodi L.; Lonstein, Joseph S.; Fleming, Alison S. (Trends in neurosciences (Regular ed.), 2017)
Ten to twenty percent of postpartum women experience anxiety or depressive disorders, which can have detrimental effects on the mother, child, and family. Little is known about the neural correlates of these affective disorders when they occur in mothers, but they do have unique neural profiles during the postpartum period compared with when they occur at other times in a woman's life. Given that the neural systems affected by postpartum anxiety and depression overlap and interact with the systems involved in maternal caregiving behaviors, mother–infant interactions are highly susceptible to disruption. Thus, there is an intricate interplay among maternal mental health, the mother–infant relationship, and the neurobiological mechanisms mediating them that needs to be the focus of future study. The highest rates of anxiety and depression occur during the first few weeks, months, or year postpartum compared with at other times in a women's life; at least one in ten postpartum women suffer from high anxiety and/or depression. Maternal anxiety and depression can have significant long-term negative effects on the mother, child, and family, but little is known about their underlying neurobiology. Neural activity in response to adult and infant emotional cues is affected by postpartum depression, pointing to a significant interplay with brain networks mediating maternal caregiving. There are both similarities and differences in the neurobiology of postpartum anxiety and depression when compared with these disorders at other times in life, indicating different etiology and suggesting that different treatments should be considered. Various treatments for postpartum depression and anxiety are available; however, more research is needed to determine whether and how these treatments improve emotion and mood through their actions on the maternal brain.